Disruption of Physiological Rhythms Persist Following Cessation of Cigarette Smoke Exposure in Mice - Vanderstocken, Gilles; Marrow, Jade P.; Allwood, Melissa A.; Stampfli, Martin R.; Simpson, Jeremy A. (Frontiers in Physiology, 2020)
Background: Physiological rhythms in mammals are essential for maintaining health, whereas disruptions may cause or exacerbate disease pathogenesis. As such, our objective was to characterize how cigarette smoke exposure affects physiological rhythms of otherwise healthy mice using telemetry and cosinor analysis. Methods: Female BALB/c mice were implanted with telemetry devices to measure body temperature, heart rate, systolic blood pressure, and activity. Following baseline measurements, mice were exposed to cigarette smoke for approximately 50 min twice daily during weekdays over 24 weeks. Physiological parameters were recorded after 1, 4, 8, and 24 weeks of exposure or after 4 weeks cessation following 4 weeks of cigarette smoke exposure. Results: Acute cigarette smoke exposure resulted in anapyrexia, and bradycardia, with divergent effects on systolic blood pressure. Long term, cigarette smoke exposure disrupted physiological rhythms after just one week, which persisted across 24 weeks of exposure (as shown by mixed effects on mesor, amplitude, acrophase, and goodness-of-fit using cosinor analysis). Four weeks of cessation was insufficient to allow full recovery of rhythms. Conclusion: Our characterization of the pathophysiology of cigarette smoke exposure on physiological rhythms of mice suggests that rhythm disruption may precede and contribute to disease pathogenesis. These findings provide a clear rationale and guide for the future use of chronotherapeutics.